Effects of varying ultrasound parameters on the oscillation of a microbubble near a boundary - Najihah, Mohd Ali; Fatimah, Dzaharudin; Erny Afiza, Alias (IOP Publishing, 2020)
Microbubbles are currently used as ultrasound contrast agents. However, microbubbles have the potential to be used in diagnostic imaging and therapeutic applications. Most numerical work on simulating microbubble oscillation involves modelling microbubbles in infinite medium whereas clinical trials and experiments involve microbubbles near a boundary such as an endothelium and blood vessels. This study will extend previous research by investigating the effects of varying the ultrasound parameters on a microbubble near a boundary. The microbubble oscillation was found to become increasingly irregular as the driving pressure amplitude is increased. The maximum amplitude of oscillation was found to decrease with increasing ultrasound frequency.